Intimate Partner Violence and Health Care-Seeking Patterns Among Female Users of Urban Adolescent Clinics - Miller, Elizabeth (Springer US, 2009)
To assess the prevalence of intimate partner violence (IPV) and associations with health care-seeking patterns among female patients of adolescent clinics, and to examine screening for IPV and IPV disclosure patterns within these clinics. A self-administered, anonymous, computerized survey was administered to female clients ages 14–20 years (N = 448) seeking care in five urban adolescent clinics, inquiring about IPV history, reasons for seeking care, and IPV screening by and IPV disclosure to providers. Two in five (40%) female urban adolescent clinic patients had experienced IPV, with 32% reporting physical and 21% reporting sexual victimization. Among IPV survivors, 45% reported abuse in their current or most recent relationship. IPV prevalence was equally high among those visiting clinics for reproductive health concerns as among those seeking care for other reasons. IPV victimization was associated with both poor current health status (AOR 1.57, 95% CI 1.03–2.40) and having foregone care in the past year (AOR 2.59, 95% CI 1.20–5.58). Recent IPV victimization was associated only with past 12 month foregone care (AOR 2.02, 95% CI 1.18–3.46). A minority (30%) reported ever being screened for IPV in a clinical setting. IPV victimization is pervasive among female adolescent clinic attendees regardless of visit type, yet IPV screening by providers appears low. Patients reporting poor health status and foregone care are more likely to have experienced IPV. IPV screening and interventions tailored for female patients of adolescent clinics are needed.